GENETIC PARAMETERS OF SELECTED RICE (Oryza Sativa L.) GERMPLASM FOR YIELD AND YIELD TRAITS - NARENDER REDDY.S and BALAJI NAIK. B, BABITHRAJ GOUD. G, SAIDA NAIK.D, ABDUL FIYAZ. R, M.M. AZAM (The Journal of Research, PJTSAU, 2023)
Food is the most basic requirement for sustaining every kind of living creature on this earth. Green revolution played an important role in reaching self-sufficiency in food production in India. The most important feature of Green revolution which led to the significant gain in the production of food grains was the development of High Yielding Varieties (HYV) (Asfaw et al., 2012).